In vitro inhibition of biofilm and virulence factor production in azole-resistant strains of Candida albicans isolated from diabetic foot by Artemisia vulgaris stabilized tin (IV) oxide nanoparticles - Zubair, Mohammad; Husain, Fohad Mabood; Al-Amri, Marai; Hasan, Imran; Hassan, Iftekhar; Albalawi, Thamer; Fatima, Farha; Khan, Altaf; Arshad, Mohammed; Alam, Pravej; Ahmad, Naved; Alatawy, Roba; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
The advent of nanotechnology has been instrumental in the development of new drugs with novel targets. Recently, metallic nanoparticles have emerged as potential candidates to combat the threat of drug-resistant infections. Diabetic foot ulcers (DFUs) are one of the dreadful complications of diabetes mellitus due to the colonization of numerous drug-resistant pathogenic microbes leading to biofilm formation. Biofilms are difficult to treat due to limited penetration and non-specificity of drugs. Therefore, in the current investigation, SnO2 nanoparticles were biosynthesized using Artemisia vulgaris (AvTO-NPs) as a stabilizing agent and were characterized using ultraviolet–visible (UV–vis) spectroscopy, Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDX). Furthermore, the efficacy of AvTO-NPs against biofilms and virulence factors of drug-resistant Candida albicans strains isolated from DFUs was assessed. AvTO-NPs displayed minimum inhibitory concentrations (MICs) ranging from 1 mg/mL to 2 mg/mL against four strains of C. albicans. AvTO-NPs significantly inhibited biofilm formation by 54.8%–87%, germ tube formation by 72%–90%, cell surface hydrophobicity by 68.2%–82.8%, and exopolysaccharide (EPS) production by 69%–86.3% in the test strains at respective 1/2xMIC. Biosynthesized NPs were effective in disrupting established mature biofilms of test strains significantly. Elevated levels of reactive oxygen species (ROS) generation in the AvTO-NPs-treated C. albicans could be the possible cause of cell death leading to biofilm inhibition. The useful insights of the present study could be exploited in the current line of treatment to mitigate the threat of biofilm-related persistent DFUs and expedite wound healing.